Digital Leadership in Organizational Transformation: Bibliometric Insights and Strategic Implications - Aliviarisa Putri Surya; Brian Emmanuel YB. Kolompoy; Shabrina Adhwa Khairunnisa; Calyqa Indie Khumeyra Liszt; Rohana Nur Aini; Muhammad Ramadhani Kesuma (Indo Publishing, 2025)
In the era of rapid technological advancement, digital leadership has emerged as a critical factor in driving organizational transformation. This study employs a bibliometric approach to analyze 1,247 Scopus-indexed articles from 2000 to 2025, utilizing VOSviewer and RStudio to map trends, patterns, and knowledge networks in digital leadership. The analysis reveals digital leadership as the central node, interconnected with five key clusters: human aspects (transformational leadership, emotional intelligence, innovation), technology (Industry 4.0, AI, blockchain), sustainability (ESG, ethical technology), education (e-learning, digital self-efficacy), and capabilities (dynamic capabilities, ambidexterity). Thematic mapping indicates a shift from crisis-driven themes (e.g., COVID-19 pandemic, virtual leadership) to mature, technology-oriented ones, with digital transformation and data-driven decision-making as motor themes. Emerging gaps include limited longitudinal studies, public sector applications, and research in developing regions like Africa and rural Asia. Indonesia contributes 15% of global publications, highlighting its potential in SME and higher education contexts. The findings underscore that digital leadership integrates strategy, human-centric approaches, technological mastery, and sustainability for holistic change. Practically, it guides leaders in formulating adaptive strategies, emphasizing ethical governance and dynamic capabilities. This research bridges theory and practice, positioning digital leadership as essential for organizational resilience in the digital economy projected to reach US130 billion in Indonesia by 2025.